Effectiveness of Guided Inquiry Learning Models Viewed From Physics Learning Achievements - Syamsudin Amir; Dewi Hikmah Marisda (Universitas Lambung Mangkurat, 2021)
This study aimed to analyze the improvement in physics learning outcomes of XI MIA State Madrasah Aliyah 2 students in East Flores after being taught using the Guided Inquiry Learning model. The type of research was a pre-experimental design with one group Pretest – Post-test. The sample in this study was saturated, namely all students of class XI MIA MAN 2 Flores. The research instrument used was a learning achievement test consisting of 30 items in multiple-choice, validated by two experts. The data obtained was then analyzed in a quantitative descriptive manner for the increased learning achievement using the N-gain test. The results showed an increase in student learning achievement, as seen from the acquisition of physics learning outcomes after the guided inquiry learning was applied. Based on the N-gain value, students’ physics learning achievement was in the medium category. Also, the acquisition of student learning outcomes has increased after the guided inquiry learning model was applied–The results of this study expected to be one of the solutions in learning physics.